One Health Outreach Efforts in Responding to Harmful Algal Blooms Issues in Hotspot Regions - Pattama Ulrich; Lindsay McGovern; Jiyoung Lee; Jason W. Stull; Lorraine Backer; Samantha Eitniear (Ohio Journal of Public Health, 2019)
Background: Globally, harmful algal blooms (HABs) in freshwater are both a historical and an ongoing issue for human, animal, and ecosystem health and have dramatic impacts on local communities. Multiple taxa of cyanobacteria, including Microcystis, Planktothrix, and Anabaena species can produce cyanotoxins. Exposure to these toxins may cause mild to severe adverse health effects. Methods: An orchestrated effort was made by a team from multiple academic disciplines, public health agencies including the Centers for Disease Control and Prevention (CDC), and community stakeholders to engage the human and animal health communities to prepare for and respond to the emerging health threat of cyanotoxins from HABs. Results: Our public health practice approaches reached multiple targeted stakeholders from public health, human, and animal health sectors. The team also helped promote the newly established nationwide One Health Harmful Algal Bloom (OHHABs) initiative in a HABs hotspot in Ohio. Conclusion: Harmful algal blooms are a One Health issue demonstrating the interactions between animal, human, and ecological health. Environmental monitoring can provide early detection of environmental events, such as HABs, that pose both public health and ecological health threats. Public health surveillance can identify human and animal health events that may be linked to local environmental events
Keywords: One Health; Harmful algal blooms; Outreach and education; Early detection; Public health surveillance